Crowdsourcing Bentham: Beyond the Traditional Boundaries of Academic History. Issue 1 (March 2014) - Causer, Tim; Terras, Melissa
Abstract : The Bentham Papers Transcription Initiative 2 (Transcribe Bentham for short) is an award-winning crowdsourced manuscript transcription initiative which engages students, researchers, and the general public with the thought and life of the philosopher and reformer, Jeremy Bentham (1748–1832), by making available digital images of his manuscripts for anyone, anywhere in the world, to transcribe. Since its launch in September 2010, over 2.6 million words have been transcribed by volunteers. This paper will examine Transcribe Bentham's contribution to humanities research and the burgeoning field of digital humanities. It will then discuss the potential for the project's volunteers to make significant new discoveries among the vast Bentham Papers collection, and examine several examples of interesting material transcribed by volunteers thus far. We demonstrate here that a crowd-sourced initiative such as Transcribe Bentham can open up activities that were traditionally viewed as academic endeavors to a wider audience interested in history, whilst uncovering new, important historical primary source material. In addition, we see this as a switch in focus for those involved in digital humanities, highlighting the possibilities in using online and social media technologies for user engagement and participation in cultural heritage.